DAMPAK KELUARNYA AMERIKA SERIKAT DARI KONVENSI SENJATA NON-KONVENSIONAL (BIOLOGIS) TERHADAP KEBIJAKAN PERSENJATAAN INTERNASIONAL ABAD KE-21: Senjata Biologis Bakteri Antraks - Jessica Bella Simatupang (2021)
The United States of America with all its capabilities, strengths and resources as a superpower has left the Biological Weapons Convention as a unified international regime that prohibits the development and production, stockpiling and use of biological weapons, legally binding and prioritizing by finding ways to ensure that biological research only used for human welfare and good. Along with the release of the United States of America from the Convention, there was an incident of bioterrorism of anthrax bacteria or Amerithrax which occurred a week after the gripping historic event, namely 9/11. Through the release of the United States from the Convention, it disrupted the biological weapons regime, so that it had an impact on the security world in the 21st century with the real threat of biological weapons in sight, so that the international weapons policy order must also be taken into account with arms control and disarmament.